Students Learner’s Perception On The Use Of Online Games Tenses In English - Sausan Sabila; Khairun Niswa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the perceptions of ninth-grade students at SMP Dharma Putra Medan toward the use of online games, specifically “Games to Learn English,” as a medium for learning the Past Tense. Utilizing a descriptive qualitative method, data were gathered through questionnaires and interviews involving ten students who had prior experience using the online game. The results show that the majority of students perceive the use of online games as fun, effective, and more engaging compared to traditional learning methods. Students reported improved understanding of verb changes from V1 to V2 and demonstrated increased motivation and confidence in learning grammar. Despite some limitations such as the lack of initial instructions and the need for teacher guidance the overall perception was positive. The findings suggest that online games can serve as an innovative and interactive learning medium, especially when supported by clear pedagogical guidance from teachers. This research highlights the importance of integrating technology into English language instruction to enhance grammar mastery and student engagement.